Reproductive health outcomes: Insights from experts and verbal autopsies - Rose Mmusi-Phetoe; Gloria Thupayagale-Tshweneagae; Oluwaseyi A. Akpor (AOSIS, 2019)
Background: Reproductive health outcomes are a measure of maternal and neonatal health. South Africa's state of maternal health is of particular concern because of the two Millennium Development Goals (MDGs) targets for monitoring maternal health, namely MDG 5a, to reduce the maternal mortality rate by three-quarters, and MDG 5b, to achieve universal access to reproductive health by 2015. Maternal mortality ratio and universal access to reproductive health receive unequal responsiveness from government. Monitoring the maternal mortality ratio has received favourable attention compared to ensuring universal access to reproductive health, hence the limited published research findings on the latter. Objectives: The purpose of this article is to report on the insights from reproductive health experts and verbal autopsies on the determinants of poor reproductive health outcomes. Method: Individual interviews with a purposively selected sample of six reproductive health experts were conducted, augmented by verbal autopsies of 12 next of kin of women and newborn babies who died within the previous 2 years period of the study. Burnard's (1995) approach of content analysis was used to analyse the data. Results: The findings revealed lack of empowerment, inaccessible reproductive health services and separation of patients living with human immune deficiency virus and those patients diagnosed with acquired immune deficiency syndrome. Conclusion: To meet the reproductive health needs, especially of the rural population, urgent attention is needed to reduce their vulnerability to the risks of poor reproductive outcomes.